Flexible ultrathin glass

By stacking two or more layers of ultra-thin glass through foldable OCA layers to form a composite layer structure, the problem of insufficient bending curvature radius and rigidity of single-layer ultra-thin glass in mobile terminal display applications is solved, and better results are achieved Flexible ultra-thin glass properties.

CN222451583UActive Publication Date: 2025-02-11BENGBU DALI TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202323121153.5
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2025-02-11
Estimated Expiration
2033-11-20

AI Technical Summary

Technical Problem

In the flexible and foldable display applications of mobile terminals, the existing single-layer ultra-thin glass cannot meet market demand, and the rigidity is insufficient or too sufficient, affecting the user experience.

Method used

Two or more ultra-thin glass (UTG) with the same or different thicknesses are stacked by foldable OCA layers to form a composite layer structure to improve the performance of flexible ultra-thin glass.

Benefits of technology

The bending curvature radius of composite flexible ultra-thin glass is achieved with a thickness similar to that of single-layer UTG, while overcoming the problem of insufficient or excessive rigidity of single-layer UTG, improving the user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222451583U_ABST
    Figure CN222451583U_ABST
Patent Text Reader

Abstract

The utility model discloses flexible ultra-thin glass which comprises one or more layers of UTGs with the same or different thickness sizes. And an OCA (Optical Clear Advanced) layer which is provided between adjacent UTGs and which constitutes a layer structure of UTG (1) + OCA (1) + UTG (2) + OCA (2) +... + OCA (n-1) + UTG (n). According to the utility model, two or more than two layers of UTG are creatively laminated through OCA to obtain the performance superior to that of a single-layer UTG, the thickness size of the UTG is similar to that of the single-layer UTG, and the preparation process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the field of ultra-thin glass (UTG) processing, and is applied to flexible and foldable active-matrix organic light-emitting diode (AMOLED) display screens or polymer dispersed liquid crystal (PDLC) dimming films of mobile terminals (such as mobile phones, tablet computers and notebooks), and in particular to flexible ultra-thin glass. Background Art

[0002] At present, most of the UTGs used in mobile terminals (such as mobile phones, tablets and notebooks) on the market are single-layer structures. The thickness is generally 30, 50, 70, 100, and 125 microns, and the average bending curvature radius is generally around 1.0, 1.5, 2.0, 2.5, and 4.0 mm. The market hopes that the bending radius of each single UTG product will fall within 1.0, 1.5, 2.0, 2.5, and 4.0 mm and the number of bends will be at least 200,000 times or more. Among them, a small number of single UTG products with a thickness of 30 and 50 microns have a bending curvature radius that cannot meet customer requirements, but this is often because the UTG body is too thin or lacks rigidity, which affects the user's touch or use. Although the touch of UTG with a thickness of 70, 100, and 125 microns can meet customer requirements, the bending curvature radius is too large and it is easy to stretch the flexible display interface of the mobile device terminal. In addition, due to the Young's modulus of UTG (73.3kN / mm 2 ) and torsional G modulus (30.1kN / mm 2 ) is too large, so it can neither meet the design requirements of mobile terminal manufacturers nor meet the needs of users.

[0003] To address the above issues, US20230226802A1 discloses a display protector comprising: a first transparent base layer having a first surface and a second surface facing each other; a second transparent substrate layer having a third surface and a fourth surface facing each other and arranged so that the third surface faces the second surface; an intermediate stress-relieving adhesive layer disposed between the second and third surfaces; a first external stress-relieving adhesive layer on the first surface; a second external stress-relieving adhesive layer on the fourth surface; and an ultra-thin glass (UTG) layer located on the first external stress-relieving adhesive layer. This solution is still based on an improvement to a single-layer UTG, but it still does not fundamentally address the shortcomings of single-layer UTG. Utility Model Content

[0004] In response to the above-mentioned problems in the prior art, the present invention provides a flexible ultra-thin glass having a thickness similar to that of a single-layer UTG but with better performance, and a preparation method thereof.

[0005] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0006] A flexible ultra-thin glass, comprising:

[0007] Two or more layers of UTG with the same or different thickness and size;

[0008] The OCA layer is set between adjacent UTGs to form the UTG (1) +OCA (1) +UTG (2) +OCA (2) +…+OCA (n-1) +UTG (n) layer structure.

[0009] The utility model creatively utilizes two or more layers of UTG to be stacked through OCA to obtain performance superior to that of a single layer of UTG, and can make the thickness of the composite flexible ultra-thin glass similar to that of a single layer of UTG, with a simple preparation process.

[0010] Furthermore, the thickness of the UTG includes but is not limited to one or a combination of two or more of 30 μm, 50 μm, 70 μm, 100 μm, and 125 μm.

[0011] Furthermore, the flexible ultra-thin glass consists of 30μm UTG+OCA+30μm UTG, 30μm UTG+OCA+50μm UTG, 30μm UTG+OCA+70μm UTG, 30μm UTG+OCA+100μm UTG, 50μm UTG+OCA+70μm UTG, or 30μm UTG+OCA+70μm UTG+OCA+30μm UTG.

[0012] If cost requirements are ignored, 30μm UTG+OCA+70μm UTG OCA+30μm UTG (three-layer UTG) can even replace 125μm, or multi-layer (i.e., N layers, the number of layers N will naturally be limited by the stringent requirements of the use scenario, the low transmittance of the UTG and OCA materials in the visible light range), composite UTG structure can be used for rollable mobile devices, such as removable handheld small-sized polymer liquid crystal dimming film (PDLC) flexible protective cover;

[0013] The present invention can utilize single-layer UTG (thickness is generally 30, 50, 70, 100, 125 μm, a total of 5 kinds, but not limited to these 5 kinds of thickness) of the same thickness or different thicknesses to stack composite double-layer or multi-layer UTG through lamination.

[0014] Utilize foldable or bendable OCA with low Young's modulus (generally 15, 25, 50, 75, 100 μm thick CEF35 or 36 series foldable or bendable OCA produced by 3M, but not limited to these 5 thicknesses and only OCA produced by 3M).

[0015] The flexible ultra-thin glass includes two or more unit components and an OCA layer between the unit components. The unit components include one or more UTG layers with the same or different thicknesses and an OCA layer between the UTG layers.

[0016] The utility model also provides a method for preparing flexible ultra-thin glass, comprising the following steps:

[0017] S1. Laminating the OCA film to the laminating surface of the UTG;

[0018] S2. Two or more UTG sheets are bonded together through OCA to form a laminated structure.

[0019] Furthermore, in S1, after the OCA film is bonded to the bonding surface of the UTG, it is placed in a defoaming equipment chamber with heating and air pressure functions, first heated at 40-50°C for 10-20 minutes; then air pressure is applied at 3-4 kgf / cm 2 Leave on for 20-30 minutes; then remove.

[0020] In S2, one side of the second UTG sheet is attached to the OCA, so that the two UTG sheets are attached together through the OCA, and then placed in the same defoaming equipment chamber with heating and air pressure function as mentioned above, heated at 50-60°C and maintained for about 15-25 minutes; then the air pressure is 3-4 kgf / cm 2 Keep it for 30 to 40 minutes, then remove it. At this point, the double-layer UTG lamination method of UTG+OCA+UTG is completed.

[0021] Further, repeat steps S1 and S2 to complete the three-layer UTG lamination method stacking and bonding product of UTG+OCA+UTG+OCA+UTG;

[0022] Or, and so on to complete UTG (1) +OCA (1) +UTG (2) +OCA (2) +…+OCA (n-1) +UTG (n) N-layer UTG lamination method superimposed bonding product.

[0023] Furthermore, in S1, the OCA is attached to the UGT bonding surface using a bonding device, and the roller pressure of the bonding device is controlled at 0.1-0.2 MPa, and the roller speed is controlled at 0.5-1.0 m / min.

[0024] Furthermore, in S2, one side of the UTG of the second and subsequent layers is attached to the OCA on the bonding surface of the UTG of the previous layer using the same bonding equipment. The roller pressure of the bonding equipment is controlled at 0.1-0.2 MPa, and the roller speed is controlled at 0.5-1.0 m / min.

[0025] Furthermore, two or more layers of composite ultra-thin flexible glass are prepared as unit components according to the methods of S1 and S2, and then the two or more unit components are laminated into multiple layers of flexible ultra-thin glass through OCA and the above-mentioned process method. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1-Figure 3 Schematic diagram of the structure of flexible ultra-thin glass. DETAILED DESCRIPTION

[0027] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0028] like Figures 1 to 3 As shown, a flexible ultra-thin glass comprises:

[0029] One or more layers of UTG1 with the same or different thickness dimensions;

[0030] OCA layer 2 is set between adjacent UTG1 to form UTG (1) +OCA (1) +UTG (2) +OCA (2) +…+OCA (n-1) +UTG (n) layer structure.

[0031] The utility model creatively utilizes two or more layers of UTG1 to be stacked through OCA2 to obtain performance superior to that of a single layer of UTG, and its thickness and size are similar to that of a single layer of UTG, and the preparation process is simple.

[0032] In practical applications, the thickness of the UTG1 includes but is not limited to one or a combination of two or more of 30 μm, 50 μm, 70 μm, 100 μm, and 125 μm.

[0033] In practical applications, two or three layers of UTG are usually considered for lamination. For example, the flexible ultra-thin glass is composed of 30μm UTG+OCA+30μm UTG, 30μm UTG+OCA+50μm UTG, 30μm UTG+OCA+70μm UTG, 30μm UTG+OCA+100μm UTG, 50μm UTG+OCA+70μm UTG, or 30μm UTG+OCA+70μm UTG+OCA+30μm UTG.

[0034] For example, 30μm UTG+OCA+30μm UTG (double-layer UTG) is used to replace the traditional single-layer 50μm flexible ultra-thin glass; 30μm UTG+OCA+50μm UTG (double-layer UTG) is used to replace the single-layer 70μm flexible ultra-thin glass for terminal mobile devices, such as smart phones and tablet computer flexible protective covers; 30μm UTG+OCA+70μm UTG (double-layer UTG) is used to replace the single-layer 100μm flexible ultra-thin glass, and 30μUTG+OCA+100μUTG (double-layer UTG) is used to replace the single-layer 125μm flexible ultra-thin glass; or 50μUTG+OCA+70μmUTG (double-layer UTG) is used to replace the single-layer 125μm flexible ultra-thin glass for terminal mobile devices, such as tablet computers and notebook flexible protective covers.

[0035] If cost is not a consideration, 30μm UTG+OCA+70μm UTG OCA+30μm UTG (three-layer UTG) can even replace a single layer of 125μm flexible ultra-thin glass, or a multi-layer (i.e., N layers, the number of layers N will naturally be limited by the stringent requirements of the use scenario, the low transmittance of the UTG and OCA materials in the visible light range, etc.) composite UTG structure can be used for large-size rollable mobile devices, such as polymer liquid crystal dimming film flexible protective cover;

[0036] The present invention can utilize single-layer UTG (thickness is generally 30, 50, 70, 100, 125 μm, a total of 5 kinds, but not limited to these 5 kinds of thickness) of the same thickness or different thicknesses to stack composite double-layer or multi-layer UTG through lamination.

[0037] Utilize foldable or bendable OCA with low Young's modulus (generally 15, 25, 50, 75, 100 μm thick CEF35 or 36 series foldable or bendable OCA produced by 3M, but not limited to these 5 thicknesses and only OCA produced by 3M).

[0038] The utility model utilizes a foldable or bendable (Folding / Bending) OCA (thickness is generally 15, 25, 50, 75, 100 microns, but not limited to these 5 thicknesses) with a low Young's modulus and places it in the middle of a thinner UTG to form a thicker composite flexible ultra-thin glass, overcoming the weakness of single-layer UTG with a thickness of 70, 100, or 125 microns, which is relatively strong in rigidity, while also solving the shortcoming of single-layer UTG with a thickness of 30 or 50 microns, which is relatively weak in rigidity.

[0039] The present invention fully utilizes the advantage of thin UTG with a small bending radius R to make up for the disadvantage of single-layer thick UTG with a large bending radius R; therefore, thin single-layer UTG is used to compound into double-layer or multi-layer structure UTG to replace only single-layer thick UTG, thereby overcoming the disadvantage of single-layer thick UTG with a large bending radius R and solving the disadvantage of single-layer thick UTG with a relatively strong rigidity.

[0040] Figure 1 The example shows a schematic diagram of the utility model wherein the multi-layer UTG is bonded into a multi-layer structure through the OCA film layer. Figure 2 Schematic diagram showing the folding of a composite structure with 4 layers of UTG flexible ultra-thin glass bonded by 3 layers of OCA film. Figure 3 is Figure 1 Based on the schematic diagram applied to the display screen, the bottom layer of the composite multi-layer flexible ultra-thin glass (shown at the top in the figure) is composited with the display layer 3 through the OCA film layer to form a schematic diagram of the display screen.

[0041] In some embodiments, the flexible ultra-thin glass includes two or more unit components and an OCA layer between the unit components, and the unit components include one or more UTG layers with the same or different thicknesses and an OCA layer between the UTG layers.

[0042] The utility model provides a method for preparing flexible ultra-thin glass, comprising the following steps:

[0043] S1. Laminating the OCA film to the laminating surface of the UTG;

[0044] S2. Laminating the bonding surfaces of two or more UTG sheets to form a laminated structure.

[0045] In some embodiments, further, in S1, after the OCA film is attached to the bonding surface of the UTG, it is placed in a defoaming equipment chamber with heating (including but not limited to electric heating, liquid medium heating, steam or gas heating, etc.) and air pressure function, first heated at 40-50°C for 10-20 minutes; then pressurized at 3-4 kgf / cm 2 Leave on for 20-30 minutes; then remove.

[0046] In S2, one side of the second UTG sheet is attached to the OCA, so that the two UTG sheets are attached together through the OCA, and then placed in a defoaming equipment chamber with heating (including but not limited to electric heating, liquid medium heating, steam or gas heating, etc.) and air pressure function, heated at 50-60°C and maintained for about 15-25 minutes; then pressurized at 3-4 kgf / cm 2 Keep it for 30 to 40 minutes, and then the double-layer UTG lamination method of UTG+OCA+UTG is completed to stack and bond the product.

[0047] When a composite product with more than three layers needs to be prepared, repeat steps S1 and S2 to complete the three-layer UTG lamination method of UTG+OCA+UTG+OCA+UTG superimposed and laminated product;

[0048] Or, and so on to complete UTG (1) +OCA (1) +UTG (2) +OCA (2) +…+OCA (n-1) +UTG (n) N-layer UTG lamination method superimposed bonding product.

[0049] In a preferred embodiment, in step S1, the OCA is attached to the UGT bonding surface using a laminating device with a roller pressure of 0.1-0.2 MPa and a roller speed of 0.5-1.0 m / min. This can eliminate bubbles and improve bonding quality.

[0050] Furthermore, in S2, one side of the second and subsequent layers of UTG is attached to the OCA on the bonding surface of the previous layer of UTG using the same bonding equipment, and the roller pressure of the bonding equipment is controlled at 0.1-0.2 MPa, and the roller speed is controlled at 0.5-1.0 m / min. It is recommended to use the bonding equipment each time the OCA film is bonded, and when the previous layer of UTG is composited to the OCA, and to control the roller pressure and speed, and then place it in a defoaming equipment furnace with heating (including but not limited to electric heating, liquid medium heating, steam or gas heating, etc.) and air pressure function to perform the above treatment to achieve the best bonding effect and quality.

[0051] In some embodiments, the present invention further provides a method for preparing flexible ultra-thin glass, comprising the following steps:

[0052] S1. Laminating the OCA film to the laminating surface of the UTG;

[0053] S2. Bond the bonding surfaces of two or more UTG sheets through OCA to form a laminated structure.

[0054] In some embodiments, further, in S1, after the OCA film is attached to the bonding surface of the UTG, it is placed in a defoaming equipment chamber with heating (including but not limited to electric heating, liquid medium heating, steam or gas heating, etc.) and air pressure function, first heated at 40-50°C for 10-20 minutes; then pressurized at 3-4 kgf / cm 2 Leave on for 20-30 minutes; then remove.

[0055] In S2, one side of the second UTG sheet is attached to the OCA, so that the two UTG sheets are attached together through the OCA, and then placed in a defoaming equipment chamber with heating (including but not limited to electric heating, liquid medium heating, steam or gas heating, etc.) and air pressure function, heated at 50-60°C and maintained for about 15-25 minutes; then pressurized at 3-4 kgf / cm 2 Keep it for 30 to 40 minutes, and then the double-layer UTG lamination method of UTG+OCA+UTG is completed to stack and bond the product.

[0056] When a composite product with an even number (4, 6, 8, etc.) of more than 4 layers needs to be prepared, repeat steps S1 and S2 to complete the (UTG+OCA+UTG)+OCA+(UTG+OCA+UTG) two-layer UTG lamination method and laminate them into a 4-layer UTG product;

[0057] When it is necessary to prepare a composite product with an odd number (5, 7, 9, etc.) of more than 5 layers, repeat steps S1 and S2 to complete a three-layer UTG (UTG+OCA+UTG+OCA+UTG)+OCA+(UTG+OCA+UTG) and double-layer lamination to form a 5-layer UTG product;

[0058] And so on to complete UTG (1) +OCA (1) +UTG (2) +OCA (2) +…+OCA (n-1) +UTG (n) N-layer UTG lamination method superimposed bonding product.

[0059] That is, first prepare two or more layers of composite ultra-thin flexible glass as unit components, and then stack the two or more unit components through OCA and the above-mentioned process method. The unit components can be prepared in advance, and then unit components with different numbers of layers can be selected and combined according to the required number of stacking layers, which can shorten the delivery cycle.

[0060] In a preferred embodiment, in step S1, the OCA is attached to the UGT bonding surface using a laminating device with a roller pressure of 0.1-0.2 MPa and a roller speed of 0.5-1.0 m / min. This can eliminate bubbles and improve bonding quality.

[0061] Furthermore, in S2, one side of the second and subsequent layers of UTG is attached to the OCA on the bonding surface of the previous layer of UTG using the same bonding equipment, and the roller pressure of the bonding equipment is controlled at 0.1-0.2 MPa, and the roller speed is controlled at 0.5-1.0 m / min. It is recommended to use the bonding equipment each time the OCA film is bonded, and when the previous layer of UTG is composited to the OCA, and to control the roller pressure and speed, and then place it in a defoaming equipment furnace with heating (including but not limited to electric heating, liquid medium heating, steam or gas heating, etc.) and air pressure function to perform the above treatment to achieve the best bonding effect and quality.

[0062] The above is only a preferred specific implementation method of the present invention, but the protection scope of the present invention is not limited to this. Any technician familiar with the technical field within the technical scope disclosed by the present invention can make equivalent replacements or changes based on the technical solution and utility model concept of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A flexible ultra-thin glass, characterized in that: include: Two or more layers of UTG with the same or different thickness and size; The OCA layer is set between adjacent UTGs to form UTG (1) +OCA (1) +UTG (2) +OCA (2) +…+OCA (n-1) +UTG (n) Layer structure; The thickness of the composite flexible ultra-thin glass is similar to that of a single-layer UTG. Two or more layers of UTG are stacked through OCA to achieve performance that is better than a single-layer UTG.

2. The flexible ultra-thin glass according to claim 1, characterized in that: The thickness of the UTG includes but is not limited to one or a combination of two or more of 30 μm, 50 μm, 70 μm, 100 μm, and 125 μm.

3. The flexible ultra-thin glass according to claim 2, characterized in that: The flexible ultra-thin glass consists of 30μm UTG+OCA+30μm UTG, 30μm UTG+OCA+50μm UTG, 30μm UTG+OCA+70μm UTG, 30μm UTG+OCA+100μmUTG, 50μm UTG+OCA+70μm UTG, or 30μm UTG+OCA+70μm UTG+OCA+30μm UTG.

4. The flexible ultra-thin glass according to any one of claims 1 to 3, characterized in that: The flexible ultra-thin glass includes two or more unit components and OCA layers between the unit components. The unit components include one or more UTGs with the same or different thicknesses and OCA layers between the UTGs.

Citation Information

Patent Citations

  • Display protector

    US20230226802A1